Opportunities and Strategies for Mainstreaming Open Data in Transport Projects in St. Petersburg - World Bank (Washington, DC, 2015)
The World Bank conducted this study of the potential for Open Transport Data in St. Petersburg as part of the preparations for the Improvement of Urban Transport Systems Project in Russia. It is principally intended for use by the St. Petersburg transportation authorities, the Federal Ministry of Transport and the Project Implementation Unit in considering and implementing open data as part of the new systems being developed as part of the Project. There are already good examples of transport information systems in St. Petersburg. Most of this information is not currently available for external use, but in the cases where it has been made available, for instance by the Agency 'Organizer of Transportation' for real-time bus information; this has been welcomed and well-used by citizens and authorities, despite some current limitations. Within the St. Petersburg component of Improvement of Urban Transport Systems Project there are plans for more transport information systems, including parking information, traffic management and passenger information systems. The conclusion of this report is that the social, economic and environmental benefits of the St. Petersburg project would be enhanced by the greater availability and use by travelers and others of the information collected by these planned systems. Making the information available as Open Transport Data and allowing it to be used for development of innovative third-party applications would be a relatively easy and cost-effective way of leveraging the planned investment to ensure that the information reached the largest number of travelers. Doing so will maximize the desired behavioral changes that drive the benefits and improve the overall return on investment.